The Effect of Financial Literacy and Personal Financial Management on Debt Level of Shopee Paylater Users with Financial Planning as A Mediation Variable on Generation Z in Cirebon City - Irfani Rahma Agustin; Krisdiana (Rescollacom (Research Collaborations Community), 2026)
This study investigates the factors influencing debt levels by analyzing the potential influence of financial literacy and personal financial management on debt levels among Shopee PayLater users, with financial planning as a mediating variable among Generation Z in Cirebon City. Data was collected from Generation Z in Cirebon City through a survey using Google Forms and distributed to respondents online. This study involved 398 respondents. The sample selection technique used purposive sampling, with Generation Z members who had or were currently using the PayLater feature in the Shopee app. Data were analyzed using SEM-PLS. The study shows that debt levels are not significantly influenced by financial literacy and financial planning, but are significantly influenced by personal financial management. Meanwhile, financial planning is significantly influenced by personal financial management and financial literacy. Furthermore, the impact of financial literacy and personal financial management on debt levels is not mediated by financial planning.